Survival and development of Lycorma delicatula (Hemiptera: Fulgoridae) on common secondary host plants differ by life stage under controlled conditions - Elsensohn, Johanna E.; Nixon, Laura J.; Urban, Julie; Jones, Sharon K.; Leskey, Tracy C. (Frontiers in Insect Science, 2023)
Host range assessment for emerging invasive insects is a vital step toward fully defining the issues the insect may pose. Spotted lanternfly (SLF) is an invasive species that is rapidly expanding its presence in the United States. The primary hosts facilitating this spread are tree of heaven, a plant from SLF’s native range, and the economically important winegrape. Black walnut is also implicated as an important and common host plant. This study investigated the survival and development of SLF on diets that included a variety of crop host plants in the presence or absence of tree of heaven. The following plant species, ‘Honeycrisp’ apple, ‘Reliance’ peach, silver maple, and tree of heaven were paired with winegrape or black walnut throughout the study. SLF had strong development and high survival on a diet of winegrape alone, and winegrape or black walnut paired with tree of heaven. Survival parameters were reduced with all other plant pairings. In particular, SLF in the winegrape and peach diet treatment did not develop past the third nymphal instar. A second experiment evaluated the survival of early and late instar nymphs and adult SLF life stages on three specialty crops – ‘Cascade’ hops, muscadine grapes, and kiwifruit over a two-week period. Nymphs survived longer than adults, with survival of first and second instar nymphs on hops not differing from the control tree of heaven treatment. The adult stage survived best on kiwi and muscadine grape. Our results show tree of heaven and winegrape were the only single plant diets evaluated that are sufficient for complete SLF development, while other host plants may require additional host or hosts of sufficient nutritional quality for SLF survival.